Copper-catalyzed remote C–H arylation of polycyclic aromatic hydrocarbons (PAHs) - Luo, Anping; Zhang, Min; Fu, Zhangyi; Lan, Jingbo; Wu, Di; You, Jingsong (Beilstein Journal of Organic Chemistry, 2020)
The regioselective C–H arylation of substituted polycyclic aromatic hydrocarbons (PAHs) is a desired but challenging task. A copper-catalyzed C7–H arylation of 1-naphthamides has been developed by using aryliodonium salts as arylating reagents. This protocol does not need to use precious metal catalysts and tolerates wide variety of functional groups. Under standard conditions, the remote C–H arylation of other PAHs including phenanthrene-9-carboxamide, pyrene-1-carboxamide and fluoranthene-3-carboxamide has also accomplished, which provides an opportunity for the development of diverse organic optoelectronic materials.
Keywords: C–H arylation; nonprecious metal catalyst; copper catalysis; polycyclic aromatic hydrocarbons (PAHs); regioselectivity

(untitled) - Wang, C.; Dong, H.; Hu, W.; Liu, Y.; Zhu, D. (Chem. Rev., 2012)

(untitled) - Sun, Z.; Ye, Q.; Chi, C.; Wu, J. (Chem. Soc. Rev., 2012)

(untitled) - Figueira-Duarte, T. M.; Müllen, K. (Chem. Rev., 2011)

(untitled) - Wu, J.; Pisula, W.; Müllen, K. (Chem. Rev., 2007)

(untitled) - Anthony, J. E. (Chem. Rev., 2006)

(untitled) - Jiang, W.; Li, Y.; Wang, Z. (Chem. Soc. Rev., 2013)

(untitled) - Stille, J. K. (Angew. Chem., Int. Ed. Engl., 1986)

(untitled) - Miyaura, N.; Suzuki, A. (Chem. Rev., 1995)

(untitled) - Li, Y.; Gao, J.; Di Motta, S.; Negri, F.; Wang, Z. (J. Am. Chem. Soc., 2010)

(untitled) - Zeng, W.; Gopalakrishna, T. Y.; Phan, H.; Tanaka, T.; Herng, T. S.; Ding, J.; Osuka, A.; Wu, J. (J. Am. Chem. Soc., 2018)

(untitled) - Hindenberg, P.; Busch, M.; Paul, A.; Bernhardt, M.; Gemessy, P.; Rominger, F.; Romero-Nieto, C. (Angew. Chem., Int. Ed., 2018)

(untitled) - Dewar, M. J. S.; Grisdale, P. J. (J. Am. Chem. Soc., 1962)

(untitled) - Yang, Y.; Lan, J.; You, J. (Chem. Rev., 2017)

(untitled) - Alberico, D.; Scott, M. E.; Lautens, M. (Chem. Rev., 2007)

(untitled) - McGlacken, G. P.; Bateman, L. M. (Chem. Soc. Rev., 2009)

(untitled) - Ackermann, L.; Vicente, R.; Kapdi, A. R. (Angew. Chem., Int. Ed., 2009)

(untitled) - Daugulis, O.; Do, H.-Q.; Shabashov, D. (Acc. Chem. Res., 2009)

(untitled) - Daugulis, O.; Zaitsev, V. G. (Angew. Chem., Int. Ed., 2005)

(untitled) - Biafora, A.; Krause, T.; Hackenberger, D.; Belitz, F.; Gooßen, L. J. (Angew. Chem., Int. Ed., 2016)

(untitled) - Shi, Y.; Zhang, L.; Lan, J.; Zhang, M.; Zhou, F.; Wei, W.; You, J. (Angew. Chem., Int. Ed., 2018)

(untitled) - Tan, G.; You, Q.; Lan, J.; You, J. (Angew. Chem., Int. Ed., 2018)

(untitled) - Huang, L.; Weix, D. J. (Org. Lett., 2016)

(untitled) - Yang, S.; Cheng, R.; Zhang, M.; Bin, Z.; You, J. (ACS Catal., 2019)

(untitled) - Moon, S.; Nishii, Y.; Miura, M. (Org. Lett., 2019)

(untitled) - Li, S.; Deng, G.-J.; Yin, F.; Li, C.-J.; Gong, H. (Org. Chem. Front., 2017)

(untitled) - Zhang, M.; Luo, A.; Shi, Y.; Su, R.; Yang, Y.; You, J. (ACS Catal., 2019)

(untitled) - Zhao, D.; Wang, W.; Yang, F.; Lan, J.; Yang, L.; Gao, G.; You, J. (Angew. Chem., Int. Ed., 2009)

(untitled) - Wu, J.; Cheng, Y.; Lan, J.; Wu, D.; Qian, S.; Yan, L.; He, Z.; Li, X.; Wang, K.; Zou, B.; You, J. (J. Am. Chem. Soc., 2016)

(untitled) - Zhang, L.; Wang, Y.; Shi, Y.; Wu, Y.; Lan, J.; Ma, W.; You, J. (ACS Catal., 2019)

(untitled) - Phipps, R. J.; Gaunt, M. J. (Science, 2009)

(untitled) - Chen, B.; Hou, X.-L.; Li, Y.-X.; Wu, Y.-D. (J. Am. Chem. Soc., 2011)

(untitled) - Yang, Y.; Li, R.; Zhao, Y.; Zhao, D.; Shi, Z. (J. Am. Chem. Soc., 2016)